2023
DOI: 10.3390/ani13182929
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Identification and Genotyping of Cryptosporidium spp. and Blastocystis sp. in Cattle in Representative Areas of Shanxi Province, North China

Yao Liang,
Ya-Ya Liu,
Jin-Jin Mei
et al.

Abstract: Both Cryptosporidium spp. and Blastocystis sp. are common intestinal protozoa, which can cause zoonotic diseases and economic losses to livestock industry. To evaluate the prevalence and genetic population structure of Cryptosporidium spp. and Blastocystis sp. in beef and dairy cattle in Shanxi Province, north China, a total of 795 fecal samples were collected from beef and dairy cattle in three representative counties in Shanxi Province, and these fecal samples were examined using molecular approaches based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 66 publications
0
2
1
Order By: Relevance
“…For dairy cattle, the Cryptosporidium spp. infection rate in the present study was higher than the corresponding rates previously reported for Ningxia Autonomous Region (1.6%, 23/1366) [31], Anhui Province (2.1%, 11/526) [32], Xinjiang Uyghur Autonomous Region (4.3%, 60/1391) [33], Shanxi Province (1.0%, 4/394) [7], Guangdong Province (4.4%, 63/1440) [34], and Gansu Province (5.1%, 58/1257) [35] but lower than those reported for Sichuan Province (14.4%, 40/278) [36], Yunnan Province (14.7%, 65/442) [37], Jiangxi Province (26.1%, 43/165) [38], Taiwan Province (26.5%, 60/226) [39], and Inner Mongolia (29.9%, 151/505) [40]. For beef cattle, the Cryptosporidium spp.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…For dairy cattle, the Cryptosporidium spp. infection rate in the present study was higher than the corresponding rates previously reported for Ningxia Autonomous Region (1.6%, 23/1366) [31], Anhui Province (2.1%, 11/526) [32], Xinjiang Uyghur Autonomous Region (4.3%, 60/1391) [33], Shanxi Province (1.0%, 4/394) [7], Guangdong Province (4.4%, 63/1440) [34], and Gansu Province (5.1%, 58/1257) [35] but lower than those reported for Sichuan Province (14.4%, 40/278) [36], Yunnan Province (14.7%, 65/442) [37], Jiangxi Province (26.1%, 43/165) [38], Taiwan Province (26.5%, 60/226) [39], and Inner Mongolia (29.9%, 151/505) [40]. For beef cattle, the Cryptosporidium spp.…”
Section: Discussioncontrasting
confidence: 78%
“…To date, 44 recognized species have been identified in the genus Cryptosporidium , and at least 12 Cryptosporidium species have been reported in cattle worldwide [ 5 ]. Among these, the dominant cattle-infecting species are C. andersoni , C. parvum , C. bovis , and C. ryanae [ 6 , 7 ]. It has also been reported that C. parvum , C. andersoni , and C. bovis can infect humans, with zoonotic cryptosporidiosis being mainly caused by C. parvum [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The five known Blastocystis subtypes (ST1 to ST4 and ST7) identified in this study are also prevalent in various animals in China [ 18 ]: ST1 in non-human primates, dogs, foxes, goats, sheep, pigs, cattle, civets, bears, and birds; ST2 in non-human primates, bears, and some captive wild animals; ST3 in non-human primates, goats, sheep, cattle, pigs, raccoon dogs, and rex rabbits; ST4 in rodents, bears, and whooper swans; and ST7 in chickens, whooper swans, and some birds [ 7 , 14 , 15 , 17 , 29 , 31 , 35 37 , 40 , 41 ]. These findings suggest the potential for zoonotic transmission of Blastocystis .…”
Section: Discussionmentioning
confidence: 99%